A Major and Stable QTL for Bacterial Wilt Resistance on Chromosome B02 Identified Using a High-Density SNP-Based Genetic Linkage Map in Cultivated Peanut Yuanza 9102 Derived Population - Wang, Lifang; Zhou, Xiaojing; Ren, Xiaoping; Huang, Li; Luo, Huaiyong; Chen, Yuning; Chen, Weigang; Liu, Nian; Liao, Boshou; Lei, Yong; Yan, Liying; Shen, Jinxiong; et al. (Frontiers in Genetics, 2018)
Bacterial wilt (BW) is one of important diseases limiting the production of peanut (Arachis hypogaea L.) worldwide. The sufficient precise information on the quantitative trait loci (QTLs) for BW resistance is essential for facilitating gene mining and applying in molecular breeding. Cultivar Yuanza 9102 is BW resistant, bred from wide cross between cultivated peanut Baisha 1016 and a wild diploid peanut species A.chacoense with BW resistance. In this study, we aim to map the major QTLs related to BW-resistance in Yuanza 9102. A high density SNP-based genetic linkage map was constructed through double-digest restriction-site-associated DNA sequencing (ddRADseq) technique based on Yuanza 9102-derived recombinant inbred lines population. The map contained 2,187 SNP markers distributed on 20 linkage groups (LGs) spanning 1566.10 cM, and showed good synteny with A genome from A.duranensis and B genome from A.ipaensis. Phenotypic frequencies of BW resistance among RIL population showed obvious bi-model distribution in four environments. Four QTLs explaining 5.49% to 23.22% phenotypic variance were identified to be all located on chromosome B02. The major QTL, qBWB02.1 (12.17-23.33% PVE), was detected in three environments showing consistent and stable expression. Furthermore, there was positive additive effect among these major and minor QTLs. The major QTL region was identified on a segment covering 2.3Mb of the pseudomolecule B02 of A. ipaensis which resides in cluster of 21 NB-LRR encoding genes. The results from the present study provides further investigation for gene discovery and marker assistant breeding in peanut.